2018
DOI: 10.1101/352484
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

DoubletFinder: Doublet detection in single-cell RNA sequencing data using artificial nearest neighbors

Abstract: Single-cell RNA sequencing (scRNA-seq) using droplet microfluidics occasionally 11 produces transcriptome data representing more than one cell. These technical artifacts are 12 caused by cell doublets formed during cell capture and occur at a frequency proportional to the 13 total number of sequenced cells. The presence of doublets can lead to spurious biological 14 conclusions, which justifies the practice of sequencing fewer cells to limit doublet formation rates. 15Here, we present a computational doublet d… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
452
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 375 publications
(459 citation statements)
references
References 17 publications
(7 reference statements)
2
452
0
Order By: Relevance
“…Criteria for doublets included having an increased number of transcripts per cell and having combined expression of canonical markers from different cell classes. 10) We retested for doublets among amacrine cells using the R package 'DoubletFinder' (McGinnis, et al 2019) with the default parameter of 7.5% as expected doublet rate. We found that ~55% of cells in clusters 16, and 60 could be doublets, although we have no way of verifying this possibility.…”
Section: Methodsmentioning
confidence: 99%
“…Criteria for doublets included having an increased number of transcripts per cell and having combined expression of canonical markers from different cell classes. 10) We retested for doublets among amacrine cells using the R package 'DoubletFinder' (McGinnis, et al 2019) with the default parameter of 7.5% as expected doublet rate. We found that ~55% of cells in clusters 16, and 60 could be doublets, although we have no way of verifying this possibility.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, PDM allows systematic variation of nanowell contents across the array, to choose conditions that maximize data quality (22). For example, controlled cell loading minimizes doublets, nanowells in which two cells are inadvertently sequenced as one, which can be major confounders in scRNA-seq experiments that assume single-cell data (25,26). Moreover, controlled printing allows us to load multiple capture beads to every well ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We envision a combination of dense exogenous barcodes via cell hashing 10 and evolved by CRISPR-Cas9 11 or intrinsic features such as clonal mutations, rearrangements, or highly correlated abundances with barcode sequence similarity metrics could be leveraged to better infer barcode multiplets. Such approaches would complement existing tools that robustly identify cell doublets 12,13 and empty droplets 14 from droplet-based scRNA-seq and further mitigate hidden confounders in single-cell data. Until then, we suggest that inferences regarding rare cell events should be corroborated across multiple channels or technologies to validate interpretation.…”
Section: Discussionmentioning
confidence: 99%